Public finance resources and regional distribution of rural development - Nagy, János; Sinóros-Szabó, Botond; Harsányi, Gergely; Nagy, Orsolya; Harsányi, Endre (Acta Agraria Debreceniensis, 2014)
Rural development, more specifically the economic development of counties have three public finance resources: the municipality, the central budgetary and the labour market fund resources. Based on the provisions of public finance, there are currently five provisions of the municipality resources of rural development: supporting settlements struggling with employment problems, supporting multi-purpose small regions, supporting settlements which are in a difficult position through no fault of their own, supporting public utility development and supporting holiday resorts. The opportunity of increasing investments is using EU funds. The structural change has a favourable direction, the proportion of the economic development program and regional developments increased in the recent years, but their share is still low. The proportion of agricultural and rural development programs which are important from the aspect of rural development is a less favourable phenomenon. Furthermore, the share of human and social development somewhat decreased, but it is still high. Apart from the regional programs, the Budget Act does not specify the regional distribution of budgets, only the professional purposes of uses, of which it is possible to conclude to which county development can be requested resources for.Between 2008 and 2011, the 13–15% share of the North Great Plain region was close to the population share of 14.7%. In 2012, there was a turn of events in which the necessity of developing the region was shown. In this year, not only the proportion, but also the absolute extent of development resources increased. Therefore, the region could use resources of 16.9 billion HUF in 2010, 31.4 billion HUF in 2011 and 56.3 billion HUF in 2012. In order to properly use these resources, determined utilisation structure is necessary to be performed. The distribution of development purposes provides an explanation for the backward position of the economic performance of Hajdú-Bihar county.Of the development resources available for four years, the region spent only 12.2% on economic development.